Host plant preference of Metcalfa pruinosa (Say, 1830) (Hemiptera: Flatidae) in the north of Hungary - Bozsik, András (Acta Agraria Debreceniensis, 2015)
Citrus flatid planthopper, a native insect to North America had for a long time a scarce economic importance there. However, being polyphagous made little damage on citrus trees and some ornamentals. In 1979 it was introduced to Italy where it established and spread quickly. It is now an invasive alien species continually spreading in South and Central Europe causing considerable damage in fruit crops and various ornamentals. Present study shows the results of a series of observations carried out from 2011 to 2015 at a number of habitats in north of Hungary. The pest could be found at each habitat but the hedge, the tree row, the gardens and the orchard/vineyard were the most infested. Frequency and population density of Metcalfa pruinosa were considerable on Asteraceae, Cannabaceae, Fabaceae, Juglandaceae, Lamiaceae, Rosaceae and Sapindaceae. Typical vegetation could be functionally classified as ornamental plants, trees/shrubs, fruit plants, weeds and feral plants. Feral plants – some of them also invasive alien species – were found at each habitat. Plant species native to America were among them the most populated. As the hedgerows were neglected, and most gardens, orchards and vineyards abandoned, these are excellent conditions for the quick and long-lasting establishment of the pest as well as they may be reservoirs to infest cultivated fruit crops and ornamentals. The hedgerow was situated along a railway line. The length of similar hedges can be merely in Pest county several hundred km, which means M. pruinosa has plenty of opportunity for spreading along the railway and infest agricultural and ornamental cultures. On the surveyed alfalfa and maize fields, accidentally very few nymphs and adults were observed. Although, the population density of M. pruinosa was considerable on many hostplants, economic damage or yield losses could not be detected. Economic or significant damage was observed only on roses, raspberries and stinging nettle. This later is cultivated in Germany and Finland. The applied horticultural oil was efficient.